PEMBINAAN KARAKTER SANTRI DIMASA PEMBELAJARAN DARING (Studi Kasus di Pondok Pesantren Perkampungan Minangkabau) - Syamsul Akmal; Sufyarma Marsidin; Rifma Rifma (Jurnal Dedikasi Pendidikan, 2022)
This research is descriptive qualitative research that describes how the impact of learning daring at the Minangkabau Islamic boarding school and how the character development of students daring the COVID-19 pandemic is developed. Daring learning conducted by Islamic boarding schools, it has other impacts on Santi, including changes in the character and behavior of students who have been instilled and grown in a student, among the changes in character that is ; the decline in the discipline of students in learning and making assignments, the decrease in the sense of togetherness that students have been accustomed to living together in Islamic boarding schools, the decline in etiquette and obedience of students in daily life and carrying out worship, Realizing this, the Minangkabau Islamic boarding schools make policies on how to build the character of students in the learning period Daring this time, among the character building carried out are; 1) Making a schedule of activities while at home; 2) Monitoring students' activities while at home by contacting students and parents, either through the GWA Group and Japri; 3) Controlling prayer and tahfizd activities for students according to the schedule at home by making daily absences through online and written absed involving parents and administrators of the nearest mosque / prayer room; 4) For students who are unable to study daring , remain in the Islamic boarding school doing learning activities and other pesantren activities, provided they comply with the Health protocol; And 5) Monitoring students' activities on social media continuously